Comparison of outcomes with and without intrastent placement during PMS surgery - Yusaku Miura; Ken Fukuda; Kenji Yamashiro (Scientific Reports)
Abstract To assess the efficacy of using a nylon suture as a stent in the PreserFlo MicroShunt (PMS) lumen to prevent postoperative hypotony, 59 eyes that underwent PMS implantation with follow-up for > 6 months were analyzed. Patients were divided into no intrastenting (NST) and intrastenting (ST) groups, with the ST group subdivided into 9 − 0 nylon suture fully placed (9 F), 9 − 0 nylon suture placement in only half of the lumen (9 H), 10 − 0 nylon suture fully placed (10 F), and 10 − 0 nylon suture placement in only half of the lumen (10 H). The distribution was as follows: 23 eyes in the NST group, 10 in the 9 F group, 9 in the 9 H group, 11 in the 10 F group, and 6 in the 10 H group. No significant differences were observed in preoperative and 6-month postoperative intraocular pressure, number of glaucoma medications, or cumulative survival rate between groups. Postoperative hypotony occurred in 13 eyes (56.5%) in the NST group, one (2.78%) in the ST group (p = 0.00014). Post-intrastent removal, hypotony occurred in 6 eyes (16.7%) in the ST group. These findings suggest that intrastent placement effectively prevents postoperative hypotony, regardless of nylon suture diameter or insertion length; however, timing is crucial as hypotony may occur after removal.